Pemanfaatan Media Interaktif Sinema-AR Sebagai Upaya Pengenalan Literasi Digital dalam Pembelajaran pada Peserta Didik Kelas V SDN Tanjung 03 Pamekasan - Alfi Mahani; Moh. Hasan Abdillah; Abdulloh Fikri; Andika Adinanda Siswoyo Andika Adinanda Siswoyo (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of holding MBKM KKNT activities using the interactive media Cinema-AR as an effort to introduce digital literacy carried out at SDN Tanjung 03 Pemekasan is 1) Providing innovative interactive learning media for teachers and students, 2) Providing understanding to teachers and students of the importance of literacy activities digital in elementary schools, 3) Implementing learning using the fun interactive learning media Cinema-AR, 4) Maximizing the use of technology in the teaching and learning process in the classroom. The subjects of this activity were 20 class V students consisting of 15 girls and 5 boys. The method used in this activity is a direct practice method through several stages including preparation, implementation and evaluation. Based on the results of the MBKM KKNT implementation, the use of Cinema-AR interactive media can increase student motivation and learning outcomes. Apart from that, learning is more fun because it is student-centered, able to provide meaningful learning experiences via smartphone, and increases students' digital literacy. During evaluation activities with the principal and teachers of SDN Tanjung 03 Pamekasan, several notes were obtained, namely sudden communication between the school and lecturers as well as the use of interactive media applications that had not been implemented by each student. So this can be used as learning material and improvement for the future.